Gemeinsam klug entscheiden – Diabetisches Fußsyndrom - Uhl, C.; Heller, A.; Rother, Ulrich; Hatzl, J.; Böckler, D. (Gefässchirurgie, 2021)
In this article the strong recommendations (grade A) of the Association of the Scientific Medical Societies in Germany (AWMF) guidelines on the topic of “National treatment guidelines for type 2 diabetes: preventive and treatment strategies for foot complications” (version 2.8, February 2010) for the areas of extended diagnostics, therapeutic procedures and amputation are summarized and discussed. Restrictively, it has to be noted that the validity of the guidelines has expired. A current version was not yet available when this article was written, therefore the authors of this article used the last available version as a reference. Additionally, the current European Society for Vascular Surgery (ESVS) guidelines on chronic limb-threatening ischemia (CLTI) were also taken into account. The grades of recommendation were assigned by a formal consensus procedure between the participating authors of the guidelines. Due to the low level of recommendation, the grade B and grade 0 recommendations are not discussed in this article.
CRIS-Team Scopus Importer:2021-04-23
Keywords: Amputation; Antibiotics; Diabetes mellitus; Revascularization; Wounds